(untitled) (Journal of Economic Research & Business Administration, 2016)
Energy is inevitable for human life and a secure and accessible supply of energy is crucial for the sustainability of modern societies.This article presents the major global findings of the use Global energy and oil consumption and provides an overview of the current and projected energy scene.Five countries have been studied in this work. These include China, Japan, Germany, USA and Kazakhstan. Together the present energy budget of these countries is roughly half that of the globe. Four of the above five countries that are discussed in this work are all net importers of energy and are heavily dependent on imports of fuel to sustain their energy demands. Their respective local oil reserves will only last 9, 6, 7 and 4 years, respectively.The demand for energy is also presented and have been analyzed by daily consumption of oil and energy.